L’alimentation des sociétés urbaines : une cure de jouvence pour l’agriculture des territoires métropolitains ? - Caroline Brand; Serge Bonnefoy (VertigO)
This paper intends to tackle the issue of the urban and peri-urban agriculture in relation to the emergent social demand concerning food. We question ourselves about the potential link the supply of food for urban societies could be for the relations between the city and its agricultural periphery.Since the Second World War, the food of industrialized societies has evolved deeply and rapidly, changing the relationship with the territory. We can observe a kind of swing between the deterritorialized and reterritorialized processes which seems currently to tilt towards the latter. We study the way food gets into the local governments agenda through the periurban agricultural policies of the cities members of the Terres en Villes network. If this introduction of food in the public agenda is usually set up by an agricultural entry, we put forward the way food could be a lever of questioning for the planning policies concerning urban regions “to live in”. Thus, we observe the very beginning of food policies which go beyond the alternative food systems policies, and create links with stakeholders other than the agricultural stakeholders that could meet around the food issue to get involved into the building of metropolitan territories.